1996
DOI: 10.1111/j.1432-1033.1996.0427h.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Susceptibilities of Fibulin‐1 and Fibulin‐2 to Cleavage by Matrix Metalloproteinases and Other Tissue Proteases

Abstract: Fibulin-1 and fibulin-2 are two novel rod-like proteins which occur either in basement membranes or in interstitial fibrils in close association with fibronectin. They were examined for their sensitivity to proteolysis by matrix metalloproteinases (stromelysin, matrilysin), circulating proteases (thrombin, plasmin, kallikrein), leucocyte elastase and mast cell chymase. Fibulin-1 (95 kDa) was readily cleaved by leucocyte elastase, weakly by matrilysin and not by the other proteases. Cleavage occurred in a domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
3

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 41 publications
4
32
0
3
Order By: Relevance
“…29 Several reports have indicated that chymase could be involved in tissue degradation by activating procollagenase 30 or by directly degrading extracellular matrix proteins such as fibronectin and fibulin-2. 31 These direct actions of chymase are independent of its AIIFA. Because the main actions reported for Ang II are cell proliferation 1 and migration 2 but not tissue degradation, higher tissue Ang II formation is unlikely to be the mechanism for the development of aneurysmal lesions, which are characterized by thinning of the medial layer of the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…29 Several reports have indicated that chymase could be involved in tissue degradation by activating procollagenase 30 or by directly degrading extracellular matrix proteins such as fibronectin and fibulin-2. 31 These direct actions of chymase are independent of its AIIFA. Because the main actions reported for Ang II are cell proliferation 1 and migration 2 but not tissue degradation, higher tissue Ang II formation is unlikely to be the mechanism for the development of aneurysmal lesions, which are characterized by thinning of the medial layer of the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the 26 kDa fragment was only detectable in ERapositive breast carcinomas and ERa-positive breast cancer- approximately 26 kDa (Sasaki et al, 1996), which may correspond to the immunoreactive fragment observed in this study. Intriguingly, elastases are also elevated in breast cancer (Kao and Stern, 1986).…”
Section: Erα-negativementioning
confidence: 93%
“…Indeed, fibulin-1 proteolysis has already been described in vitro (Sasaki et al, 1996) and in studies of cultured skin fibroblastic cells (Debeer et al, 2002), as well as in the skin of mice exhibiting 2,4-dinitrofluorobenzene-induced chronic contact dermatitis (Kusubata et al, 1999). Other explanations for the origin of the N-terminal fibulin-1 fragments include differential alternative splicing and/or the usage of internal ribosome entry sites.…”
Section: Erα-negativementioning
confidence: 99%
“…Poly(A) ϩ RNA was recovered from total RNA with an RNA Polytex-Kit (Qiagen Tissue extraction and protein analysis. Tissues from various organs were extracted following a previously established protocol (45). Protein extracts were used for immunoblotting and radioimmunoassays.…”
Section: Methodsmentioning
confidence: 99%